Evaluating TOPAS for the calculation of backscatter factors for low energy x-ray beams. (2nd October 2018) - Hewson, E A; Butson, M J; Hill, R
Abstract: For low x-ray energies, backscatter is an important parameter for determining the absorbed dose, making accurate knowledge of backscatter factors (BSFs) essential. BSFs can be difficult to measure experimentally so published values are often derived using Monte Carlo methods. This study evaluated the Monte Carlo code TOPAS as a tool for dose calculations for kilovoltage x-rays, and for calculating BSFs for energies ranging from 50 to 280 kVp. BSFs were also measured experimentally for comparison using Gafchromic EBT3 film and optically stimulated luminescence dosimeters (OSLs). The BSFs calculated using TOPAS were found to be consistent within 2% of the values published in the AAPM TG-61 protocol. The TOPAS BSF calculations were also found to be consistent with film measurements, typically within 2%. The largest discrepancy measured was 5% for the 3 cm field size and 180 kVp beam. OSLs were found to overestimate BSFs for large field sizes and high energies so were found to be unsuitable for BSF measurements with differences of up to 18%.